2014
DOI: 10.4028/www.scientific.net/amm.543-547.1901
|View full text |Cite
|
Sign up to set email alerts
|

The Improved Fuzzy Analytic Hierarchy Process

Abstract: In FAHP, discontinuous scale, such as 0.1-0.9 scale, is usually used to get fuzzy judgment matrix. But when evaluating system is complex or index systems are too many, we may get stuck in a comparison dilemma by using 0.1-0.9 scale, resulting in a fuzzy judgment matrix of poor consistency. This paper improved 0.1-0.9 scale and established 0-1 continuous scale. We first apply 0-1 three scales to get a comparison matrix, and then converted it into a fuzzy judgment matrix according to 0-1 continuous scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Step 3: Calculate the evaluation index weights and the weight of each cell layer. The evaluation indicators are divided into qualitative and quantitative indicators in the calculation process, where the qualitative indicators are sequentially compared two by two and labelled based on the 1-9 scales and e 0/4 -e 8/4 scales; additionally, the quantitative indicators require the use of relevant calculation methods (Lee et al, 2018;Zhang et al, 2014), and the proposed formula is shown in equation ( 1).…”
Section: Calculation Of Subjective Weights Using the Improved Ahpmentioning
confidence: 99%
“…Step 3: Calculate the evaluation index weights and the weight of each cell layer. The evaluation indicators are divided into qualitative and quantitative indicators in the calculation process, where the qualitative indicators are sequentially compared two by two and labelled based on the 1-9 scales and e 0/4 -e 8/4 scales; additionally, the quantitative indicators require the use of relevant calculation methods (Lee et al, 2018;Zhang et al, 2014), and the proposed formula is shown in equation ( 1).…”
Section: Calculation Of Subjective Weights Using the Improved Ahpmentioning
confidence: 99%
“…Step 3: Calculate the evaluation index weights and the weight of each cell layer. The evaluation indicators are divided into qualitative and quantitative indicators in the calculation process, where the qualitative indicators are sequentially compared two by two and labelled based on the 1-9 scales and e 0/4 -e 8/4 scales; additionally, the quantitative indicators require the use of relevant calculation methods (Lee et al, 2018;Zhang et al, 2014), and the proposed formula…”
Section: Calculation Of Subjective Weights Using the Improved Ahpmentioning
confidence: 99%